2021
DOI: 10.3389/fphys.2021.660068
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise: A Novel Tool to Protect Mitochondrial Health

Abstract: Mitochondrial dysfunction is a crucial contributor to heart diseases. Alterations in energetic metabolism affect crucial homeostatic processes, such asATP production, the generation of reactive oxygen species, and the release of pro-apoptotic factors, associated with metabolic abnormalities. In response to energetic deficiency, the cardiomyocytes activate the Mitochondrial Quality Control (MQC), a critical process in maintaining mitochondrial health. This process is compromised in cardiovascular diseases depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 157 publications
(199 reference statements)
0
45
0
Order By: Relevance
“…Approaches to improve mitochondrial function are divided into two groups: pharmacological and non-pharmacological interventions. Non-drug strategies are primarily aimed at shifting lifestyle towards more physically active behavior, which has a beneficial effect on improving mitochondrial function and increasing the number of mitochondria [65]. Research has shown that complex lifestyle interventions can improve cognitive function in older people at increased risk of dementia.…”
Section: Potential Therapeutic Strategies To Restore Mitochondrial Fu...mentioning
confidence: 99%
“…Approaches to improve mitochondrial function are divided into two groups: pharmacological and non-pharmacological interventions. Non-drug strategies are primarily aimed at shifting lifestyle towards more physically active behavior, which has a beneficial effect on improving mitochondrial function and increasing the number of mitochondria [65]. Research has shown that complex lifestyle interventions can improve cognitive function in older people at increased risk of dementia.…”
Section: Potential Therapeutic Strategies To Restore Mitochondrial Fu...mentioning
confidence: 99%
“…Exercise has strong pleiotropic effects on mitochondrial health in many cell types, including neurons and non-neuronal cells in the central and peripheral nervous systems [ 48 ]. Exercise increases mitochondrial antioxidant capacity, electron transport chain efficiency, and biogenesis and decreases oxidative stress and mtDNA damage [ 49 ]. Specifically, exercise promoted neurogenesis and hippocampal plasticity via improvements in mitochondrial function in a mouse model [ 50 ].…”
Section: Neurophysiological Mechanismsmentioning
confidence: 99%
“…Moreover, previous studies have demonstrated that physical exercise (resistance and aerobic training) influence mitochondrial function and immune–inflammatory responses [ 124 ] through an important cellular process called mitochondria quality control [ 125 ]. This process includes the modification of mitochondrial proteins, mitochondrial dynamics, and autophagy [ 126 ], which leads to the control of the production of free radicals by creating antioxidant networks [ 127 ] (see Figure 2 ). As previously discussed, BDNF signalling through exercise plays a major role in neurogenesis, and the maintenance of cerebral BDNF levels is important for effective neural function [ 128 ].…”
Section: The Inhibition Of Oxidative Stress Through Exercise: the Inf...mentioning
confidence: 99%
“…Moreover, Erickson et al [ 143 ] reported that PA training improves spatial memory function and reduces age-related hippocampal tissue loss in older adults. Furthermore, it is well established that PA is a potent stimulus to induce different signalling pathways that produce phenotypic changes in the mitochondria, leading to greater muscle health [ 126 ]. However, different methodological aspects of PA such as intensity and duration can exert different mitochondrial changes [ 140 ].…”
Section: The Inhibition Of Oxidative Stress Through Exercise: the Inf...mentioning
confidence: 99%